ab-plane tunneling and Andreev spectroscopy of superconducting gap an pseudogap in - D`yachenko, A.I.; Tarenkov, V.Yu.; Szymczak, R.; Szymczak, H.; Abal`oshev, A.V.; Lewandowski, S.J.; Leonyuk, L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
We have measured the temperature dependence of gap features revealed by Andreev reflection (Ds) and by tunneling (D) in the ab-plane of optimally and slightly overdoped microcrystals of (BiPb)2Sr2Ca2Cu3O10+d (Bi2223) with critical temperature Tc = 110-115 K, and Bi2Sr2CaCu2O8+d (Bi2212) with Tc = 80-84 K. The tunneling conductance of a Bi2223-insulator-Bi2223 junction shows peaks at the 2D gap voltage, as well as dips and broad humps at other voltages. In Bi2223, similarly to the well-known Bi2212 spectra, the energies corresponding to 2D, to the dip, and to the hump structure are in the ratio 2:3:4. This confirms that the dip and hump features are generic to the high-temperature superconductors, irrespective of the number of CuO2 layers or the BiO superstructure. On the other hand, in both compounds the D(T) and Ds(T) dependences are completely different, and we conclude that the two entities are of different natures.